Breathable, washable and wearable woven-structured triboelectric nanogenerators utilizing electrospun nanofibers for biomechanical energy harvesting and self-powered sensing. (February 2021) - Guan, Xiaoyang; Xu, Bingang; Wu, Mengjie; Jing, Titao; Yang, Yujue; Gao, Yuanyuan
Abstract: With the rapid advancement in wearable electronics, energy harvesting devices based on triboelectric nanogenerators (TENGs) have been intensively investigated for providing sustainable power supply for them. However, the fabrication of wearable TENGs still remains great challenges, such as flexibility, breathability and washability. Here, a route to develop a new kind of woven-structured triboelectric nanogenerator (WS-TENG) with a facile, low-cost, and scalable electrospinning technique is reported. The WS-TENG is fabricated with commercial stainless-steel yarns wrapped by electrospun polyamide 66 nanofiber and poly(vinylidenefluoride-co-trifluoroethylene) nanofiber, respectively. Triggered by diversified friction materials under a working principle of freestanding mode, the open-circuit voltage, short-circuit current and maximum instantaneous power density from the WS-TENG can reach up to 166 V, 8.5 µA and 93 mW/m 2, respectively. By virtue of high flexibility, desirable breathability, washability and excellent durability, the fabricated WS-TENG is demonstrated to be a reliable power textile to light up 58 light-emitting diodes (LED) connected serially, charge commercial capacitors and drive portable electronics. A smart glove with stitched WS-TENGs is made to detect finger motion in different circumstances. The work presents a new approach for self-powered textiles with potential applications in biomechanical energy harvesting, wearable electronics and human motion monitoring. Graphical Abstract: A brand-new type of nanofiber-based triboelectric nanogenerator with simple woven-fabric structure, remarkable breathability and washability, diversified triggering materials and reliable durability was designed and realized by utilizing novel core-shell yarns composed of functional nanofiber coating layer and core electrode yarn by a versatile electrospinning and scalable weaving strategy for the first time, and its promising potentials for harvesting biomechanical energy and self-powered sensing applications were demonstrated. ga1 Highlights: A brand-new type of nanofiber-based TENG with woven fabric structure was prepared by an electrospinning and weaving strategy. The obtained WS-TENGs possess remarkable air and moisture permeability, robust durability and good washability. The WS-TENGs can be triggered by diverse frictional materials and influential factors on output performance were studied. Fixed at different positions of human body, WS-TENGs show application potential for biomechanical energy harvesting. A smart-glove with stitched WS-TENGs was fabricated to demonstrate the capacity for self-powered sensing application.